Antihypertensive Prescription Pattern in the Department of Nephrology Khyber Teaching Hospital Peshawar (Medical Forum Monthly, 2024)
Objective: To find the prescription pattern of antihypertensive drugs in the department of Nephrology Khyber Teaching Hospital PeshawarStudy Design: Observational / cross sectional study.Place and Duration of Study: This study was conducted at the outpatient department of nephrology Khyber Teaching Hospital Peshawar from January 2018 to March 2018.Materials and Methods: 200 patients suffering from hypertension were included in the study. We examined the frequency and proportion of various antihypertensive drugs as mono therapy, combination therapy and fixed drug combinations (FDCs).Results: Most frequently prescribed antihypertensive drugs were CCBs (65%) followed by diuretics (54%), beta blockers (50.5%), ARBs (26%) and ACEIs (21%) respectively. 57.5% were using two drugs and most commonly used FDCs was diuretics with ACEI.Conclusion: Calcium channel blockers are mostly prescribed while alpha blockers are the least prescribed antihypertensives drugs.